To What Extent Does the Home-Visit Program Impact Students’ Knowledge ff Poverty, Family Systems, and Child Development? - Brennan, Mary; Jarzynski, Rebecca L.; Mueller, Kathryn (My University, 2019)
This study aimed to assess how student knowledge is impacted by high-impact practice. Undergraduate students took part within an existing home-visit program targeting children in low-income, high-risk families. Their knowledge of family systems, child development, and communication as they relate to living in poverty was assessed pre-, mid-, and post-program.
Color poster with text, charts, and graphs.
Keywords: Home visit; Low-income families; College students; Field experience programs; Posters